"I'm Not Fragile. I'm Not Limited": Career Aspirations of Youth With Perinatally Acquired HIV. (April 2018) - Fair, Cynthia D.; Rupp, Sophie; Mitchell, Joanna; Gatto, Amy
Although children born with perinatally acquired HIV (PHIV) are now living into adulthood, little is known about their transition into the workforce and the ways they develop career aspirations. In this phenomenological study, 35 youth with PHIV (mean age 20.7) completed semistructured interviews regarding their career aspirations which were transcribed and coded for emergent themes using grounded theory. Approximately half of the participants were employed at the time of the interview. Sixteen participants aspired to work in helping professions. Others sought employment in the arts or business sector. Participants indicated that parents/guardians and medical providers were generally supportive of their career interests. Providers and social workers often helped them find jobs and construct resumes. Thirteen participants indicated that their HIV status had little impact on their career aspirations. Others believed HIV-related challenges related to transmission, physical difficulties, and emotional turmoil limited their ability to pursue certain careers. Several felt inspired to fight against HIV-related stigma/discrimination. It is important to encourage youth with PHIV to prepare for their future by routinely holding conversations regarding their career goals.